Analisis Permasalahan Yang Dihadapi Oleh Pelaku Usaha Mikro Agar Berkembang Menjadi Usaha Kecil (Scalling Up) Pada Umkm Di 14 Kecamatan Di Kabupaten Bogor - Rainanto, Bambang Hengky (Jurnal Ilmiah Manajemen Kesatuan, 2019)
The existence of micro, small and medium enterprises (UMKM) has significant importance in supporting and promoting economy development in Indonesia. Other than encouraging economic growth, these UMKM have proven to reduce unemployment. UMKM contribution to gross domestic products develops from previously 57.84% to 60.34% in the last five years. The absorption of employment also rises from 96.99% to 97.22% in the same period. Of the three divisions of enterprises, micro enterprise is leading by the number followed by small and lastly medium enterprise. In terms of encouraging micro business to grow into small (scaling up), it is necessary to seek issues mostly encountered by micro business subjects. The research was administered using survey method with descriptive analysis to micro business subjects in 14 regions in Kabupaten Bogor. This is one of the efforts to clearly visualize the problems and obstacles in the development of micro business. The results found that aspects of marketing, funding, production, human resources, materials, product and production legal aspect, financial and distribution managements are among the biggest problems for the micro business in Kabupaten Bogor.